Consumption of energy drinks in a group of young athletes - Nowak, Dariusz; Gośliński, Michał; Popławski, Cezary (Journal of Education, Health and Sport, 2019)
Energy drinks (EDs) are very popular among adolescents and young adults. Excessive consumption of EDs may cause various health risks due to the presence of caffeine and sugar. The aim of this study was to evaluate the consumption of energy drinks in a group of young athletes. Obtained results showed that 56% of participants in Bydgoszcz and 89% in Toruń drink EDs. Quite frequent consumption declared 37% and 29% of young athletes in Bydgoszcz and Toruń, respectively. Participants make the decision of EDs consumption with no particular reason or when they are thirsty. Unfortunately, some students mixed energy drinks with alcohol (AMED).